Development of red rice germ extract-loaded microcapsules by complex coacervation using alternative proteins and polysaccharide as wall materials - Bhattarai, Susma; Katekhong, Wattinee; Tan, Chin Ping; Klinkesorn, Utai; Peanparkdee, Methavee (Elsevier, 2025)
Red jasmine rice germ extract is rich in phenolic compounds, naturally pigmented, hydrophilic, and possesses potent antioxidant properties. However, these beneficial attributes are highly susceptible to degradation by heat and light. This study aimed to microencapsulate the rice extract using a blend of whey protein concentrate (WPC), silkworm pupae protein (SPP), or moringa leaf protein (MLP) with gum arabic (GA) as sustainable wall materials via complex coacervation. The formation of microcapsules at different protein-polysaccharide ratios and pH levels was extensively examined using ζ-potential, turbidity, and coacervate yield analysis. Results indicated that a protein-polysaccharide ratio of 3:1 facilitated optimal complex formation at pH 3.5 for WPC/GA and pH 3.0 for SPP/GA and MLP/GA, primarily driven by strong electrostatic interactions. The encapsulation efficiency of the microcapsules ranged from 40 % to 65 %, with SPP achieving the highest efficiency. The microcapsules were further subjected to in vitro digestion, simulating the oral, gastric, and intestinal phases. Encapsulation significantly enhanced the total phenolic content and antioxidant activity of the rice extract after gastrointestinal digestion compared to the non-encapsulated extract, as confirmed by DPPH, FRAP, and ABTS assays. Notably, microcapsules formulated with SPP exhibited the highest encapsulation efficiency and retained superior antioxidant properties following in vitro digestion.